Meningkatkan Kemampuan Berfikir Tingkat Tinggi (HOTS) Siswa Kelas XI IPA SMA Negeri 2 Bagan Sinembah T.P 2020/2021 Dengan Penerapan Model Siklus Belajar 5E Melalui Materi Sistem Ekskresi Dalam Proses Pembelajaran Daring - Salsa Dila Hakim Rangkuti; Armadani Armadani; Egithania Br Ketaren; Linawati Siregar; Rena Novita (Mahesa Research Center, 2021)
This study aims to improve the thinking skills of high-level students through the use of the 5E cycle learning model in class XI IPA students of SMA Negeri 2 Bagan Sinembah TP Riau 2020/2021 (PT) using the Kemmis and Mc.Taggart method to improve. The subjects of this study were 36 students of class XI IPA-1. This classroom action research was carried out in 2 cycles, with each cycle consisting of 1 session. Cycle I discusses the human excretory system, and Cycle II discusses disorders of the human excretory system. The data collection techniques used were tests of higher order thinking skills and teacher activity observation sheets in the application of the 5E cycle learning model and data analysis techniques with individual and classical percentage analysis. The results showed that the use of the 5E cycle learning model was able to improve high thinking skills (HOTS) of class XI science students at SMA Negeri Bagan Sinembah TP 2020/2021 Riau with a material removal system and increasing teacher activity in the learning process. The percentage of thinking ability (HOTS) from 50% in the first cycle increased to 67% in the second cycle in the good category, in the 85% cycle it increased to 92%, the percentage in the very good category was accepted.